Cadre, Stakeholder, and Community Support in the Best Practice Model for Quality Family Village - Rahayuwati, Laili; Komariah, Maria; Hendrawati, Sri; Agustiana, Ekawati; Agiustien, Ghita Megalia; Manahan, Sautman; Nur, Gina Zulfah (Universitas Padjadjaran, 2025)
Pangadegan Village, Sumedang Regency, has a high stunting rate. To overcome this, the village government and various related parties took strategic steps by making innovations in implementing the stunting reduction acceleration program by implementing the Quality Family Village Best Practice Model Program. This study aims to provide an overview of cadre support and active community participation in successfully implementing the Best Practice Model for accelerating stunting reduction in the Quality Family Village of Pangadegan Village. This research is a qualitative study involving residents, cadres, and stakeholders. Data collection was conducted using interviews and focus group discussions (FGDs). This research provides an overview and analysis of the implementation of the Best Practice Model Program, which is presented in seven themes by covering programs that support the acceleration of stunting reduction, understanding, and changes in community behaviour as well as the support and active participation of cadres, stakeholders, and the community. The study results show that the implementation of the Quality Family Village Best Practice Model Program in Pangadegan Village is effective with the support and active participation of cadres, stakeholders, and the community in accelerating stunting reduction in Pangadegan Village Quality Family Village.Keywords: Cadre, Community, Model Best Practice, Quality Family Village, Stakeholder, Stunting, Support.